Potential probiotic evaluation of two Lactobacillus plantarum strains isolated from Indonesian fermented food and fruit - A’liyatur Rosyidah; Heddy Julistiono (The East Java Biological Society, 2017)
Two Lactobacillus plantarum strains, InaCC B122 and InaCC B128, isolated from Indonesian fermented food, “dadih” and fruit were evaluated for probiotic potential. These two lactobacilli strains were subjected to a series of in vitro test to assess their surviving capability in gastrointestinal track and antimicrobial activity. The test included acid and bile salt tolerance, adhesion to the yeast Saccharomyces cereviseae cells, heat resistance and antimicrobial activity against Mycobacterium smegmatis, Escherichia coli, and Staphylococcus aureus. Both strains were able to grow under acid and bile salt condition for 24 h. Co-aggregation percentage of strain InaCC B122 and InaCC B128 against the yeast cells was 52.3 % and 53.8 % respec-tively. Heat treatments (45 ℃ for 30 min. and 55 ℃ for 15 min.) did not affect co-aggregation percentages. Their supernatants had antimicrobial activity against M. smegmatis, E. coli and S. aureus with MIC of 5 %, 10 % and 10 % respectively. In conclusion, based on this assessment, these strains are good candidate for probiotic.